Communist in Padang Panjang (1923-1989) - Sovia Nelisia; Siti Fatimah; Azmi Fitrisia (Fakultas Ilmu Pendidikan UNP)
This research discusses how the communists enter the Padang Panjang city which is very famous for its Islam and is the first place of Islamic modification in Sumatra. And how these communist figures influenced the people and santri of Sumatra Thawalib and saw how these communist propagandists took action in exploiting the mass media to convey their ideas. This research uses historical research method with steps (1) Heuristik that is searching and collecting information obtained as data source . (2) Criticism of the source is done by testing the authenticity and kesahihhan data. (3) Conducting analysis and interpretation of data. (4) Histotography of the presentation of research results. This study aims to see how the communists enter Padang Panjang and are accepted by the fanatical community of Islam. The study shows that in the 20th century the communists entered Padang Panjang city which is very famous for its Islamic interest is that this communist understanding was brought by a religious teacher in Sumatra Thawalib and adopted by his santrinya they regard unis in accordance with the teachings of Islam which they call the science kuminih.